The impact of cognitive load on prospective and retrospective time estimates at long durations: An investigation using a visual and memory search paradigm. - Walker, Jesika A.; Aswad, Mohammed; Lacroix, Guy (Memory & Cognition, 2022)
As human beings, we are bound by time. It is essential for daily functioning, and yet our ability to keep track of time is influenced by a myriad of factors (Block & Zakay, 1997, Psychonomic Bulletin & Review, 4[2], 184–197). First and foremost, time estimation has been found to depend on whether participants estimate the time prospectively or retrospectively (Hicks et al., 1976, The American Journal of Psychology, 89[4], 719–730). However, there is a paucity of research investigating differences between these two conditions in tasks over two minutes (Tobin et al., 2010, PLOS ONE, 5[2], Article e9271). Moreover, estimates have also been shown to be influenced by cognitive load. We thus investigated participants' ability to keep track of time during a visual and memory search task and manipulated its difficulty and duration. Two hundred and ninety-two participants performed the task for 8 or 58 minutes. Participants in the prospective time judgment condition were forewarned of an impending time estimate, whereas participants in the retrospective condition were not. Cognitive load was manipulated and assessed by altering the task's difficulty. The results revealed a higher overestimation of time in the prospective condition compared with the retrospective condition. However, this was found in the 8-minute task only. Overall, participants significantly overestimated the duration of the 8-minute task and underestimated the 58-minute task. Finally, cognitive load had no effect on participants' time estimates. Thus, the well-known cross-over interaction between cognitive load and estimation paradigm (Block et al., 2010, Acta Psychologica, 134[3], 330–343) did not extend to a longer duration in this experiment.